2017
DOI: 10.3748/wjg.v23.i41.7359
|View full text |Cite
|
Sign up to set email alerts
|

Region-dependent effects of diabetes and insulin-replacement on neuronal nitric oxide synthase- and heme oxygenase-immunoreactive submucous neurons

Abstract: AIMTo investigate the intestinal segment-specific effects of diabetes and insulin replacement on the density of different subpopulations of submucous neurons.METHODSTen weeks after the onset of type 1 diabetes samples were taken from the duodenum, ileum and colon of streptozotocin-induce diabetic, insulin-treated diabetic and sex- and age-matched control rats. Whole-mount preparations of submucous plexus were prepared from the different gut segments for quantitative fluorescent immunohistochemistry. The follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…A previous study with obese mice (ob/ob) showed that neither the density nor area of the total population in the duodenum myenteric neurons are perturbed, but differences could be observed in the myenteric neuronal‐specific subpopulations (Spangeus & El‐Salhy, 2001). Notably, in streptozotocin‐induced diabetic animals, an increase in the nitrergic neuronal population of the submucosal plexus in the jejunum and colon was reported (Bódi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study with obese mice (ob/ob) showed that neither the density nor area of the total population in the duodenum myenteric neurons are perturbed, but differences could be observed in the myenteric neuronal‐specific subpopulations (Spangeus & El‐Salhy, 2001). Notably, in streptozotocin‐induced diabetic animals, an increase in the nitrergic neuronal population of the submucosal plexus in the jejunum and colon was reported (Bódi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the submucous plexus, the proportion of nNOS-immunoreactive neurons was doubled in the ileum and tripled in the colon, but not in the duodenum of diabetic rats, while the total neuronal number remained unchanged, suggesting neurochemical adaptation of submucous neurons [35]. These results emphasize that the diabetic state affects the two enteric plexuses differentially.…”
Section: Pathophysiology Of Nitrergic Enteric Neuronsmentioning
confidence: 97%
“…Moreover, it is proved that HO1ÀIR and HO2ÀIR neurons are present in very small amounts in the submucous plexus of the small intestine. 31 The slight expression of these antioxidants may contribute to significantly lower protection against different pathological stimuli in the ileum.…”
Section: Gut Region-specific Oxidative Environment and Antioxidant Capacity Under Physiological Conditionsmentioning
confidence: 99%